If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2x + -61 = x + 3 Reorder the terms: -61 + 2x = x + 3 Reorder the terms: -61 + 2x = 3 + x Solving -61 + 2x = 3 + x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1x' to each side of the equation. -61 + 2x + -1x = 3 + x + -1x Combine like terms: 2x + -1x = 1x -61 + 1x = 3 + x + -1x Combine like terms: x + -1x = 0 -61 + 1x = 3 + 0 -61 + 1x = 3 Add '61' to each side of the equation. -61 + 61 + 1x = 3 + 61 Combine like terms: -61 + 61 = 0 0 + 1x = 3 + 61 1x = 3 + 61 Combine like terms: 3 + 61 = 64 1x = 64 Divide each side by '1'. x = 64 Simplifying x = 64
| 12x+48=22 | | N+15=31 | | 100/20/78000= | | c^2+5+4=0 | | 6=2*.5+5 | | 4t=33 | | 4t=30 | | 4z=-6z-30 | | -4a-(3a-2)=-12 | | .75x+8y=24 | | -4x+9+5-2x+5-2x= | | 50-3x+80=7x | | 8x+4y=14 | | 20/100*78000= | | -4x+9+5-2x+5-2x=X | | 6g+5-3g-7= | | 100/2*78000= | | 10x=14.08 | | 16x=3x-52 | | 19+8x=x | | 6=7-n | | 56+v=34 | | 7x-10=6c(11-2x) | | 3t+6=15 | | 3(6x-7)+6(5x-8)= | | t+(3t+5)=9 | | 8x+24y=14 | | -4a-9=2a+15 | | 3x+3-6x=6-(3x+3) | | 2y=5*-2+10 | | 7x-3+8x-19=180 | | 2(x-3)+5x=-2x+12 |